Penegakan Hukum Pidana Terhadap Tindak Pidana Korupsi Di Indonesia: Analisis Yuridis Normatif Berdasarkan Undang-Undang Nomor 31 Tahun 1999 Jo. Undang-Undang Nomor 20 Tahun 2001 - Ahmad Zakiy Nugraha (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Corruption is the most detrimental criminal act to state finances and damages the foundations of social life in Indonesia. The legal issues raised in this study are how the normative regulation of corruption in Indonesian positive law is structured and why law enforcement against corruptors is still not optimal. This study aims to analyze and describe the regulation of corruption in Law Number 31 of 1999 jo. Law Number 20 of 2001, and to analyze factors affecting the effectiveness of its enforcement. The methodology used is normative juridical research with statutory and conceptual approaches. The results show that corruption regulations in Indonesia have comprehensively regulated various forms of corruption. However, its enforcement remains hindered by weak inter-agency coordination, judicial inconsistency, and low deterrent effects. Synergy between KPK, Prosecutors, and Police, along with reform of the evidence system, is needed to optimize anti-corruption efforts.